Adsorption of lactic acid onto three ionic liquid‐modified porous polymers. Issue 3 (3rd December 2012) - Tang, Baokun; Tian, Minglei; Row, Kyung Ho
Abstract Three ionic liquid (IL)‐modified porous polymers were synthesized and used for the adsorption of lactic acid. The experimental adsorption kinetics and equilibrium data from the IL‐modified polymers were obtained. The kinetic study revealed a low temperature to be advantageous to the adsorption process. The dependence of the level of lactic acid adsorption on the amount of polymer, initial lactic acid concentration, and pH was examined at equilibrium. The maximum efficiency was obtained using the maximum adsorbent dose. A comparison of lactic acid adsorption at different pH revealed anion exchange to be the main interaction between the lactic acid and polymers, not molecular adsorption. The amounts adsorbed were fitted to the Langmuir, Freundlich, and Temkin equations. The equilibrium data for modified polymers (imidazole modified polymer, methylimidazole modified polymer, and ethylimidazole modified polymer) were best represented by the Langmuir and Freundlich isotherm with R2 values of 0.99. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013